Halal Destination Image, Electronic Word of Mouth (e-WOM), and Revisit Intention at Tourist Destinations in Sumenep Regency - Yustina Chrismardani; Mohammad Arief (Quantitative Economics and Management Studies, 2022)
It is still rare for research to include the concept of halal tourism in measuring the destination image and using the halal destination image as a function of the revisit intention. By looking at the importance of measuring revisit intention as part of tourism marketing, this study aims to analyze: (1) the direct effect of e-WOM on the halal destination image; (2) the direct effect of e-WOM on revisit intention; (3) the direct effect of the halal destination image on the revisit intention; and (4) the indirect effect of e-WOM on the revisit intention, through the halal destination image. The study was conducted on 100 tourists who has visited and seen social media of tourist destinations in Sumenep Regency. Data analysis was performed with Path Analysis. From the analysis, the results obtained that e-WOM has a direct effect on the halal destination image. The halal destination image has a direct effect on the revisit intention at tourist destinations in Sumenep Regency, and the halal destination image mediates the indirect effect of e-WOM on the revisit intention.